2021
DOI: 10.1161/hypertensionaha.120.16002
|View full text |Cite
|
Sign up to set email alerts
|

Central Ang II (Angiotensin II)-Mediated Sympathoexcitation

Abstract: Central infusion of Ang II (angiotensin II) has been associated with increased sympathetic outflow resulting in neurogenic hypertension. In the present study, we appraised whether the chronic increase in central Ang II activates the paraventricular nucleus of the hypothalamus (PVN) resulting in elevated sympathetic tone and altered baro- and chemoreflexes. Further, we evaluated the contribution of HIF-1α (hypoxia-inducible factor-1α), a transcription factor involved in enhancing the expression of N-methyl-D-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 57 publications
(48 reference statements)
2
13
0
Order By: Relevance
“…We have previously shown that HR can decrease with age in normotensive rodents ( Zubcevic et al, 2009 ). Thus, attenuation of these time-dependent changes in HF IBI and HR in the Ang II group suggests deregulation of cardiac parasympathetic drive after Ang II infusion, as it has previously been reported ( Miller and Arnold, 2019 ; Dorey et al, 2020 ; Sharma et al, 2021 ). However, this effect of Ang II on HF IBI was not significantly affected by ICV NaHS co-treatments, suggesting lesser effects of central infusion of NaHS on parasympathetic control of BP in our study.…”
Section: Discussionsupporting
confidence: 75%
“…We have previously shown that HR can decrease with age in normotensive rodents ( Zubcevic et al, 2009 ). Thus, attenuation of these time-dependent changes in HF IBI and HR in the Ang II group suggests deregulation of cardiac parasympathetic drive after Ang II infusion, as it has previously been reported ( Miller and Arnold, 2019 ; Dorey et al, 2020 ; Sharma et al, 2021 ). However, this effect of Ang II on HF IBI was not significantly affected by ICV NaHS co-treatments, suggesting lesser effects of central infusion of NaHS on parasympathetic control of BP in our study.…”
Section: Discussionsupporting
confidence: 75%
“…In line with this, surprisingly, lactacystin did not reduce but increased blood pressure and fibrotic rebuilding in the left ventricle (Simko et al, 2017). Thus, lactacystin administration-induced BP elevation was recently characterized as a novel model of experimental hypertension (Vrankova et al, 2010;Simko et al, 2017;Sharma et al, 2020). Proteasome inhibition may cause hypertension either because of an increased endogenous protein inhibitor of neuronal nitric oxide synthase, leading to decreased NO bioavailability in the paraventricular nucleus (Sharma et al, 2020), or from tyrosine hydroxylase upregulation and activation in the hypothalamus and brainstem (Congo Carbajosa et al, 2015), both resulting in increased sympathetic outflow.…”
Section: Quantitative Analysis Of Kidney Fibrosismentioning
confidence: 72%
“…Thus, lactacystin administration-induced BP elevation was recently characterized as a novel model of experimental hypertension (Vrankova et al, 2010;Simko et al, 2017;Sharma et al, 2020). Proteasome inhibition may cause hypertension either because of an increased endogenous protein inhibitor of neuronal nitric oxide synthase, leading to decreased NO bioavailability in the paraventricular nucleus (Sharma et al, 2020), or from tyrosine hydroxylase upregulation and activation in the hypothalamus and brainstem (Congo Carbajosa et al, 2015), both resulting in increased sympathetic outflow. Bearing in mind the remodeling of the heart (Simko et al, 2017) and aorta (Vrankova et al, 2010) in this model, it seems to be of importance to disclose whether lactacystin could act in a similar pro-proliferative way in hypertensive kidneys.…”
Section: Quantitative Analysis Of Kidney Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic stress-induced persistent hypertension is mediated by an increased sympathetic outflow also through α-2δ-1-linked NMDARs in the PVN [81]. Hypoxia-inducible factor-1α participates in the Ang II-NMDAR-mediated activation of presympathetic neurons in the PVN by upregulating NMDAR expression, ulti-mately increasing sympathetic outflow [82]. Evidently, the RAS in the PVN independently exerts a pressor effect and synergistically interacts with other processes, such as oxidative stress and glutamatergic and GABAergic synapses.…”
Section: Effect Of Ras On Blood Pressure In the Pvnmentioning
confidence: 99%